Glycerol residue - a rich source of glycerol and medium chain fatty acids - Ooi, T. L.; Yong, K. C.; Abu Hassan, Hazimah; Abdullah, Dzulkefly Kuang; Wan Yunus, Wan Md. Zin (Japan Oil Chemists' Society, 2004)
Glycerol residue, a by-product of glycerol refining from a palm kernel oil methyl ester plant, was found to be a good source of glycerol and medium chain fatty acids. From analyses of twelve samples, it was found to contain, on average, 20.2 % glycerol and 6.6 % fatty acids. The fatty acids comprised mainly C8:0 (30.3 %), C10:0 (9.4 %) and C12:0 (40.8 %).